Modification of single-nucleotide polymorphism in a fully humanized CYP3A mouse by genome editing technology. Issue 1 (December 2017) - Abe, Satoshi; Kobayashi, Kaoru; Oji, Asami; Sakuma, Tetsushi; Kazuki, Kanako; Takehara, Shoko; Nakamura, Kazuomi; Okada, Azusa; Tsukazaki, Yasuko; Senda, Naoto; Honma, Kazuhisa; Yamamoto, Takashi; et al.
Abstract Cytochrome P450, family 3, subfamily A (CYP3A) enzymes metabolize approximately 50% of commercially available drugs. Recently, we developed fully humanized transchromosomic (Tc) CYP3A mice with the CYP3A cluster includingCYP3A4, CYP3A5, CYP3A7, andCYP3A43 . Our humanized CYP3A mice have theCYP3A5*3 (g.6986G) allele, resulting in the almost absence of CYP3A5 protein expression in the liver and intestine. To produce model mice for predicting CYP3A5′s contribution to pharmacokinetics, we performed a single-nucleotide polymorphism (SNP) modification ofCYP3A5 (g.6986G to A, *3 to *1) on the CYP3A cluster using genome editing in both mouse ES cells and fertilized eggs, and produced humanized CYP3A5*1 mice recapitulating theCYP3A5*1 carrier phenotype in humans. The humanized CYP3A mouse withCYP3A5*1 is the first Tc mouse for predicting the SNP effect on pharmacokinetics in humans. The combination of Tc technology and genome editing enables the production of useful humanized models that reflect humans with different SNPs.